Nostalgia of sports tourism: with a modeling approach at the individual level of nostalgia through the attitudes and behavioral intentions of young spectators of the premier football league - Zareh, Saeed; Zarei, Ali; Tojari, Farshad (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2021)
Background and Aim:  Recent researches list various factors to understand the behavior of sports fans, which include motivation, satisfaction and loyalty. Therefore, the aim of the research was to investigate the nostalgia of sports tourism with the approach of modeling at the individual level of nostalgia through the attitudes and behavioral intentions of the spectators of the premier football league. Research method: This research is applied in terms of purpose and descriptive-analytical in terms of method, and its statistical population was all the spectators present at the home games of the football teams of the Iranian premier league (N= 500,000). The statistical sample for the individual level model was randomly selected from among all the spectators present at the home games of the football teams of Iran's premier football league, and 518 completed questionnaires were returned. The data collection tool was the revised questionnaire of Chu (2014). The validity of the questionnaires was confirmed by 5 experts in the field of sports management. The reliability of questionnaires was obtained using Cronbach's alpha coefficient for nostalgia questionnaire α=0.93, attitude α=0.91, behavioral intentions α=0.89. For data analysis, SPSS 20 software package was used to perform descriptive statistics and Lisrel version 0.9 to perform inferential statistics (CFA, SEM). CFA results showed that all the components in the model were confirmed. Results: SEM results showed that nostalgia and its components have a significant effect on the audience's attitude and behavioral intentions in the individual level model (Sig